Changes in surface layer of silicon wafers from diamond scratching. Issue 1 (2015) - Zhang, Zhenyu; Wang, Bo; Kang, Renke; Zhang, Bi; Guo, Dongming
Abstract: This study investigates diamond scratching at a high speed comparable to that in a grinding process on an ultraprecision grinder. Diamond tips are prepared for the study. The scratched silicon wafer is observed for changes in the surface layer with transmission electron microscopy. The observation discovers that an amorphous layer is formed on top of the pristine Si-I phase before the onset of chip formation. This discovery is different from the previous findings in which a damaged silicon layer is identified underneath the amorphous layer. Furthermore, no high pressure phase is found before the onset of chip formation.